Exploring the relationship between activities and emotional experience using a diary in a mental health inpatient setting. (20th February 2017) - Folke, Fredrik; Hursti, Timo; Kanter, Jonathan W.; Arinell, Hans; Tungström, Stefan; Söderberg, Per; Ekselius, Lisa
Abstract: Mental health inpatient milieus have repeatedly been found to be associated with passivity, social disengagement, and low levels of interaction with staff. However, little is known about patients' experiences related to different ward activities. In the present study, we aimed to study the reports of activities and associated experiences of patients admitted to acute psychiatric inpatient wards. Disengaged, inactive, and solitary activities were hypothesized to be associated with less reward and more distress than their counterparts. We also aimed to investigate if such activities predicted distress, and if they were associated with clinical severity. Participants ( n  = 102) recorded their activities along with concurrent ratings of reward and distress in a structured 1‐day diary, and nurses provided clinical severity ratings. On average, 3.74 of the 11 hours assessed (34%) were spent doing nothing, only 0.88 hours (8%) were spent with staff, and most of the time was spent in solitude. Doing nothing, being alone, and passivity were associated with the greatest levels of distress and lowest levels of reward, whereas informal socializing demonstrated the opposite pattern. Distress was not predicted by activity or reward when adjusting for baseline distress. Clinical severity was not associated with the amount of time spent alone or the experience of reward during activity. In conclusion, the risk for passivity and social disengagement during admission prevails. This activity pattern could have detrimental emotional consequences and warrants action, but more studies are needed to determine if activity actually precedes emotional experience.